Peran Kepemimpinan dan Disiplin Kerja Karyawan Pada Kinerja Pelayanan di PT. X Surabaya - Rina Dewi; Mochamad Indrawan; Achmad Daengs Gs (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Effective leadership and employee discipline are essential to maintaining a productive and professional workplace environment. Leaders are expected to open up two-way communication so that employees can fully understand the Company's goals in achieving performance. Companies need to have a clear and consistent approach to employee discipline to ensure that employees understand company policies and comply with performance expectations. In addition, employee discipline helps identify and correct behavior or actions that are detrimental to the organization.